Global Trends In Good Corporate Governance And Tax Risk Management: A Bibliometric Analysis Using Vosviewer - Angelia Nirwana Sari, Laras; Pawitri, Wiwit; Subagdja, Achmad (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This study aims to map how scientific research on the relationship between Good Corporate Governance (GCG) and Tax Risk Management has evolved in recent years and to identify key thematic clusters in this area. Methodology: A Systematic Literature Review (SLR) was conducted using Publish or Perish software for data retrieval and VOSviewer for bibliometric mapping and visualization. Results: The analysis revealed an upward trend in scholarly publications linking GCG to tax risk. Findings: Findings indicate that strong corporate governance plays a crucial role in minimizing tax-related risks through mechanisms such as audit committees, board oversight, and disclosure practices. Novelty: This study contributes novelty by combining two bibliometric tools to systematically explore this interdisciplinary domain. Originality: The originality lies in its structured synthesis of existing literature, providing a global perspective on how GCG can be leveraged to manage tax risks. Conclusion: In conclusion, research on GCG and tax risk is expanding, but further empirical and sector-specific studies are needed to build more robust governance-tax frameworks.